DEXAMETHASONE AND GRANULOCYTE COLONY-STIMULATING FACTOR CHANGE THE REGENERATIVE NEUROMA MORPHOLOGY - Grabovyi, O.M.; Nevmerzhytska, N.M.; Shepelev, S.E.; Kondaurova, H.Yu. (World of Medicine and Biology, 2023)
Regenerative neuroma of the sciatic nerve is characterized by typical cellular composition and the Schwann cells and fibroblasts ratio. Dexamethasone or granulocyte colony-stimulating factor applied in the early stages of regenerative neuroma formation affects the final state of the stromal component of the neuroma and slightly increases Schwann cells in it. The combined use of dexamethasone and granulocyte colony-stimulating factor potentiates the effect of granulocyte colony-stimulating factor on increasing the number of Schwann cells in the regenerative neuroma and delays its involution. It leads to a noticeable change in the regenerative neuroma composition towards the neural component.